JAPANESE OVERSEAS POLICY ON THE IMPLEMENTATION OF WATER DEFENSE IDENTIFICATION ZONE (ADIZ) TIONGKOK - Srinanda, Wahyu; Rani, Faisyal (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
This study aims to look at Japan's response to the establishment of China's air defense (adiz) identification zone. Where China on November 23, 2013 announced it had set a unilateral air defense identification zone in most of the east China sea air region which included airspace above the senkaku islands which is currently being fierce with Japan. Besides the unilateral determination of the Chinese ADIZ zone, it also overlaps with Japan's ADIZ. Japan considers that this Chinese action has threatened the country's territorial security.This study uses the theory of foreign policy, the concept of security dilemma seen from the neorealist perspective. The level of analysis is the nation-state with Japan and China as the main actors. The type of research in this study is descriptive type and data collection techniques are library studies. Data is obtained through books, journals, scientific articles, official documents and internet media.The results of this study are that Japan, through its foreign policy, responded to China's ADIZ by rejecting the establishment of the Chinese ADIZ because it was considered to have threatened Japanese territorial sovereignty. In order to safeguard its territorial territory, the Japanese government tried to revive the Japanese military by conducting a re-representation of article 9 of the Japanese constitution which was the basis of Japanese military fascism after the Second World War defeat. And Japan also strengthened security cooperation with the United States by reviewing The Guidelines for Japan-U.S. Defense Cooperation (Guidelines) in 2015Keywords: Air Defense Identification Zone (ADIZ), my island disputes, foreign policy